A Ralstonia solanacearum type III effector alters the actin and microtubule cytoskeleton to promote bacterial virulence in plants. - Rachel Hiles; Abigail Rogers; Namrata Jaiswal; Weiwei Zhang; Jules Butchacas; Marcus V Merfa; Taylor Klass; Pragya Barua; Venkatesh P Thirumalaikumar; Jonathan M Jacobs; Christopher J Staiger; Matthew Helm; et al. (PLoS Pathogens)
Cellular responses to biotic stress frequently involve signaling pathways that are conserved across eukaryotes. These pathways include the cytoskeleton, a proteinaceous network that senses external cues at the cell surface and signals to interior cellular components. During biotic stress, dynamic cytoskeletal rearrangements serve as a platform from which early immune-associated processes are organized and activated. Bacterial pathogens of plants and animals use proteins called type III effectors (T3Es) to interfere with host immune signaling, thereby promoting virulence. We previously found that RipU, a T3E from the soilborne phytobacterial pathogen Ralstonia solanacearum, co-localizes with the plant cytoskeleton. Here, we show that RipU from R. solanacearum K60 (RipUK60) associated with and altered the organization of both the actin and microtubule cytoskeleton. We found that pharmacological disruption of the tomato (Solanum lycopersicum) cytoskeleton promoted R. solanacearum K60 colonization. Importantly, tomato plants inoculated with R. solanacearum K60 lacking RipUK60 (ΔripUK60) had reduced wilting symptoms and significantly reduced root colonization when compared to plants inoculated with wild-type R. solanacearum K60. Collectively, our data suggest that R. solanacearum K60 uses the type III effector RipUK60 to remodel cytoskeletal organization, thereby promoting pathogen virulence.